Contemporary management of acute coronary syndromes: does the practice match the evidence? The global registry of acute coronary events (GRACE). Issue 3 (14th February 2005) - Carruthers, K F; Dabbous, O H; Flather, M D; Starkey, I; Jacob, A; MacLeod, D; Fox, K A A
Abstract : Objective: To determine to what extent evidence based guidelines are followed in the management of acute coronary syndromes (ACS) in the UK, elsewhere in Europe, and multinationally, and what the outcomes are. Design: Multinational, prospective, observational registry (GRACE, global registry of acute coronary events) with six months' follow up. Setting: Patients presenting to a cluster of hospitals. The study was designed to collect data representative of the full spectrum of ACS in specific geographic populations. Patients: Patients admitted with a working diagnosis of unstable angina or suspected myocardial infarction (MI). Main outcome measures: Death during hospitalisation and at six months' follow up (adjusted for baseline risks). Results: In ST elevation MI, reperfusion was applied more often in the UK (71%) than in Europe (65%) and multinationally (59%) (p < 0.01). However, this was almost entirely by lytic treatment, in contrast with elsewhere (primary percutaneous coronary intervention 1%, 29%, 16%, respectively). Statins were applied more frequently in the UK for all classes of patients with ACS (p < 0.0001). In contrast there was lower use of revascularisation procedures in non-ST MI (20% v 37% v 28%, respectively) and glycoprotein IIb/IIIa antagonists (6% v 25% v 26%, respectively). In-hospital death rates, adjusted for baseline risk, were not significantly different but six month death rates were higher in the UK for ST elevation MI (7.2% UK, 4.3% Europe, 5.3% multinationally; p < 0.0001) and non-ST elevation MI (7.5%, 6.2%, and 6.7%, respectively; p  =  0.012, UK v Europe). Conclusions: Current management of ACS in the UK more closely follows the recommendations of the National Service Framework than British or European guidelines. Differences in practice may account for the observed higher event rates in the UK after hospital discharge.